5

I was having trouble with the following problem in boolean algebra i.e.

A+A'B = A+B

I need to prove the above section. I mean its already reduced i can't reduce it further.

kishanio
  • 6,979
  • 8
  • 25
  • 33

3 Answers3

13

A+A'B = A.1 + A'B = A.(1+B)+A'B = A.1+A.B+A'B = A + B.(A+A') = A + B.1 = A + B

rarief
  • 131
  • 1
  • 3
7

A + A'B = (A + A') (A + B) = 1 (A + B) = A + B

timrau
  • 22,578
  • 4
  • 51
  • 64
1

First taking NOT on both sides and then apply De-Morgan's Law on both sides:

L.H.S=

(A+A'B)'
=(A'.(A'B)')
=(A'.(A+B')) //again applied de-morgan's law in previous step
=(A'.A + A'B')
=A'B'

also apply De-morgans on RHS
(A+B)'
=A'B'

Thus LHS = RHS

Afaq
  • 1,146
  • 1
  • 13
  • 25